Ten-year trend of care practices, morbidities and survival of very preterm neonates in the Malaysian National Neonatal Registry: a retrospective cohort study - Azanna Ahmad Kamar; Pauline Choo; Nem Yun Boo; Seok Chiong Chee; Siew Hong Neoh; Eric Boon-Kuang Ang; Ee Lee Ang; Farah Inaz Syed-Abdullah; Ann Cheng Wong (BMJ Publishing Group, 2021)
Objectives To determine a 10-year trend of survival, morbidities and care practices, and predictors of in-hospital mortality in very preterm neonates (VPTN, gestation 22 to <32 weeks) in the Malaysian National Neonatal Registry.Design Retrospective cohort study.Setting 43 Malaysian neonatal intensive care units.Patients 29 010 VPTN (without major malformations) admitted between 1 January 2009 and 31 December 2018.Main outcome measures Care practices, survival, admission hypothermia (AH, <36.5°C), late-onset sepsis (LOS), pneumothorax, necrotising enterocolitis grade 2 or 3 (NEC), severe intraventricular haemorrhage (sIVH, grade 3 or 4) and bronchopulmonary dysplasia (BPD).Results During this 10-year period, there was increased use of antenatal steroid (ANS), lower segment caesarean section (LSCS) and early continuous positive airway pressure (eCPAP); but decreased use of surfactant therapy. Survival had increased from 72% to -83.9%. The following morbidities had decreased: LOS (from 27.9% to 7.1%), pneumothorax (from 6.0% to 2.7%), NEC (from 8.1% to 4.7%) and sIVH (from 12.2% to 7.5%). However, moderately severe AH (32.0°C-35.9°C) and BPD had increased. Multiple logistic regression analyses showed that lower birth weight, no ANS, no LSCS, admission to neonatal intensive care unit with <100 VPTN admissions/year, no surfactant therapy, no eCPAP, moderate and severe AH, LOS, pneumothorax, NEC and sIVH were significant predictors of mortality.Conclusion Survival and major morbidities had improved modestly. Failure to use ANS, LSCS, eCPAP and surfactant therapy, and failure to prevent AH and LOS increased risk of mortality.